Alternation of Resting-State Functional Connectivity Between Visual Cortex and Hypothalamus in Guinea Pigs With Experimental Glucocorticoid Enhanced Myopia After the Treatment of Electroacupuncture - Zhang, Tao; Jiang, Qian; Xu, Furu; Zhang, Ruixue; Liu, Dezheng; Guo, Dadong; Wu, Jianfeng; Wen, Ying; Wang, Xingrong; Jiang, Wenjun; Bi, Hongsheng (Frontiers in Neuroinformatics, 2021)
Excessive glucocorticoids (GC) may lead to the aggravation of several basic diseases including myopia, due to plasma hormone imbalances associated with the hypothalamic-pituitary-adrenal axis (HPAA). Electroacupuncture (EA) is an effective therapeutic method to treat many diseases, althoughit remains unclear whether EA at acupoints on the foot or back would be effective in treating eye diseases. It was recently found that visual cortex activity for responses to visual stimuli with spatial frequency and resting-state functional connectivity (FC) between the supramarginal gyrus and rostrolateral prefrontal cortex was significantly reduced in patients with high myopia. The present study aims to investigate the role of the alternation of resting-state FC among the bilateral visual cortex and hypothalamus in exerting anti-mypoia effects of EA in GC-enhanced lens-induced myopic (LIM) guinea pigs such that the mechanisms of EA to treat GC-enhanced myopia at Shenshu (BL23) acupoints can be probed.To confirm the effects of EA, ocular parameters including axial length and GC-associated physiological parameters such as animal appearance, behavior, bodyweight and levels of four HPAA-associated plasma hormones (free triiodothyronine (FT3), free thyroxine (FT4), estradiol (E2) and testosterone (T)) were also collected. Increased resting-state FC between the left and right visual cortex was detected in GC-enhanced lens-induced myopic guinea pigs with EA at BL23acupoints (LIM+GC+EA)guinea pigs compared to GC-enhanced lens-induced myopic guinea pigs with EA at sham acupoints (LIM+GC+Sham) guinea pigs, as well assuppressed myopia and recovery of symptoms initially caused byoverdose of GC. Recovered symptomsincluded improved animal appearance, behavior, bodyweight and HPAA-associated plasma hormone levels were observed afterfour weeks of EA treatment. In contrast, the LIM+GC+Sham group showeddecreased FC with elongation of axial length for myopizationas compared to the control group and LIM group, and exhibiting a deterioration in physiological parameters including reduced body weight and balance disruption in the four measured HPAA-associated plasma hormones. Our findings suggest that EA could effectively treat GC-enhanced myopia by increasing resting-state FC between the left and right visual cortex, which may be pivotal to further understanding the application and mechanisms of EA in treating GC-enhanced myopia.